ANALISIS PENGARUH PENGELOLAAN KEUANGAN, PENGGUNAAN FINTECH DAN LITERASI KEUANGAN TERHADAP KINERJA USAHA - AGUSLINA ZALUKHU; Risca Azmiana (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the effect of financial management, the use of fintech, and financial literacy on business performance in MSMEs in Batu Aji District, Batam City. The background of this research is based on the strategic role of MSMEs in the national economy, but they still face various obstacles in financial management, utilization of financial technology, and low levels of financial literacy. This research uses a quantitative method with a sample size of 131 respondents taken using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that partially, financial management, use of fintech, and financial literacy had a positive and significant effect on business performance. Simultaneously, these three independent variables also have a significant effect on MSME business performance. These findings indicate the importance of improving financial management skills, fintech utilization, and financial literacy in improving the competitiveness and sustainability of MSME businesses in Batu Aji sub-district.